USE OF INTERNET RESOURCES IN TEACHING FORENSIC MEDICINE (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
During the years of independence, the modernization of educational processes in our country and the upbringing of the younger generation have become an integral part of state policy. Of course, at present, in the development of educational processes, an important role is played by the study of the description and classification of regulatory documents, the skills of industry workers in accordance with the requirements of the time, in increasing the potential of higher education professors and teachers, strengthening their qualifications.